Respiratory Symptoms, Sensitization, and Exposure–Response Relationships in Spray Painters Exposed to Isocyanates - Pronk, Anjoeka (American Thoracic Society, 2007)
Rationale: Associations between oligomeric isocyanate exposure, sensitization, and respiratory disease have received little attention, despite the extensive use of isocyanate oligomers. Objectives: To investigate exposure–response relationships of respiratory symptoms and sensitization in a large population occupationally exposed to isocyanate oligomers during spray painting. Methods: The prevalence of respiratory symptoms and sensitization was assessed in 581 workers in the spray-painting industry. Personal exposure was estimated by combining personal task-based inhalatory exposure measurements and time activity information. Specific IgE and IgG to hexamethylene diisocyanate (HDI) were assessed in serum by ImmunoCAP assay and enzyme immunoassays using vapor and liquid phase HDI–human serum albumin (HDI–HSA) and HSA conjugates prepared with oligomeric HDI. Measurements and Main Results: Respiratory symptoms were more prevalent in exposed workers than among comparison office workers. Log–linear exposure–response associations were found for asthmalike symptoms, chronic obstructive pulmonary disease–like symptoms, and work-related chest tightness (prevalence ratios for an interquartile range increase in exposure of 1.2, 1.3 and 2.0, respectively; P ⩽ 0.05). The prevalence of specific IgE sensitization was low (up to 4.2% in spray painters). Nevertheless, IgE to N100 (oligomeric HDI)–HSA was associated with exposure and work-related chest tightness. The prevalence of specific IgG was higher (2–50.4%) and strongly associated with exposure. Conclusions: The results provide evidence of exposure–response relationships for both work-related and non–work-related respiratory symptoms and specific sensitization in a population exposed to oligomers of HDI. Specific IgE was found in only a minority of symptomatic individuals. Specific IgG seems to be merely an indicator of exposure.